Use of Silver Nitrate in Superior Limbic Keratoconjunctivitis - Sania Munawar, Mian Muhammad Shafique, Muhammad Khalil, Tayyaba Gul Malik (Pakistan Journal of Ophthalmology, 2018)
A 38 years old Pakistani female presented in outpatient department with a history of irritation and redness in both eyes for the last five months. It was associated with foreign body sensations and watering of both eyes. She had been using different eye drops but there was no recovery. There was no history of contact lens use. Slit lamp examination revealed superior limbal congestion in the form of inverted trapezoid, centered at 12 O’clock. Examination of the upper tarsal conjunctiva showed velvety congestion and papillae formation. Patient was prescribed topical lubricants and fluorometholone eye drops. Follow up after three weeks showed mild recovery. We applied 0.5% silver nitrate solution as a trial to the upper tarsal conjunctiva. The patient showed marked improvement in congestion after three weeks. During this period she used lubricant eye drops.